Quality of acute psychedelic experience predicts therapeutic efficacy of psilocybin for treatment-resistant depression - Roseman,L; Nutt,DJ; Carhart-Harris,RL (Frontiers in Pharmacology, 2018)
Introduction: It is a basic principle of the ‘psychedelic’ treatment model that the quality of the acute experience mediateslong-term improvements in mental health. In the present paper we sought to test this using data from a clinical trial assessingpsilocybin for treatment-resistant depression (TRD). In line with previous reports, we hypothesized that the occurrence andmagnitude of Oceanic Boundlessness (OBN) (sharing features with mystical-type experience) and Dread of Ego Dissolution (DED)(similar to anxiety) would predict long-term positive outcomes, whereas sensory perceptual effects would not.Material and Methods: Twenty patients with treatment resistant depression underwent treatment with psilocybin (two separatesessions: 10mg and 25mg psilocybin). The Altered States of Consciousness (ASC) questionnaire was used to assess the quality ofexperiences in the 25mg psilocybin session. From the ASC, the dimensions OBN and DED were used to measure the mystical-typeand challenging experiences, respectively. The Self-Reported Quick Inventory of Depressive Symptoms (QIDS-SR) at 5 weeks servedas the endpoint clinical outcome measure, as in later time points some of the subjects had gone on to receive new treatments,thus confounding inferences. In a repeated measure ANOVA, Time was the within-subject factor (independent variable), withQIDS-SR as the within-subject dependent variable in baseline, 1-day, 1-week, 5-weeks. OBN and DED were independent variables.OBN-by-time and DED-by-time interactions were the primary outcomes of interest.Results: For the interaction of OBN and DED with Time (QIDS-SR as dependent variable), the main effect and the effects at each timepoint compared to baseline were all significant (p = 0.002 and p = 0.003, respectively, for main effects), confirming our mainhypothesis. Furthermore, Pearson’s correlation of OBN with QIDS-SR (5 weeks) was specific compared to perceptual dimensions ofthe ASC (p < 0.05).Discussion: This repo